2021
DOI: 10.1007/s11356-021-16678-1
|View full text |Cite
|
Sign up to set email alerts
|

Novel bioavailability-based risk assessment of Cd in earthworms and leeches utilizing in vitro digestion/Caco-2 and MDCK cells

Abstract: In the present study, the oral bioavailability of cadmium (Cd) in earthworms and leeches was investigated through in vitro physiologically based extraction test (PBET) digestion/Caco2 and MDKC cell models. We are the first to create an innovative assessment strategy which has capacity to offer a more precise evaluation of Cd-associated health risks in traditional animal medicines (TAMs), by combinational usage of bioavailable Cd levels, the duration and frequency of the exposure to TAMs obtained by questionnai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…The CR results also indicated that the carcinogenic risk from Pb and As in animal herbal medicines, except Pheretima, was below the acceptable lifetime risk. In 2021, Zuo Tian-tian et al [ 65 ] developed a refined risk assessment strategy for heavy metals in TAMs based on bioavailability. The strategy incorporated factors such as bioavailability level of heavy metals, exposure time of TAMs, storm rate frequency, and safety factors, resulting in a more realistic and accurate assessment of the health risk of Cd in TAMs.…”
Section: Risk Assessment Of Heavy Metals and Harmful Elements In Mtcm...mentioning
confidence: 99%
“…The CR results also indicated that the carcinogenic risk from Pb and As in animal herbal medicines, except Pheretima, was below the acceptable lifetime risk. In 2021, Zuo Tian-tian et al [ 65 ] developed a refined risk assessment strategy for heavy metals in TAMs based on bioavailability. The strategy incorporated factors such as bioavailability level of heavy metals, exposure time of TAMs, storm rate frequency, and safety factors, resulting in a more realistic and accurate assessment of the health risk of Cd in TAMs.…”
Section: Risk Assessment Of Heavy Metals and Harmful Elements In Mtcm...mentioning
confidence: 99%